2007
DOI: 10.1103/physrevlett.99.130401
|View full text |Cite
|
Sign up to set email alerts
|

Resonant Einstein–de Haas Effect in a Rubidium Condensate

Abstract: We theoretically consider a spin polarized, optically trapped condensate of 87Rb atoms in F=1. We observe a transfer of atoms to other Zeeman states due to the dipolar interaction which couples the spin and the orbital degrees of freedom. Therefore the transferred atoms acquire an orbital angular momentum. This is a realization of the Einstein-de Haas effect in systems of cold gases. We find resonances which make this phenomenon observable even in very weak dipolar systems, when the Zeeman energy difference on… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
85
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(88 citation statements)
references
References 17 publications
3
85
0
Order By: Relevance
“…Previous studies on spinor-dipolar BECs have shown that the interplay between spin-dependent interaction and DDI leads to rich topological defects and spin structures [28][29][30][31][32][33][34]. Consequently, it is of particular interest to explore the effects of long-rang and anisotropic DDI on such a spin-orbit coupled system, which has recently drawn considerable attentions.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on spinor-dipolar BECs have shown that the interplay between spin-dependent interaction and DDI leads to rich topological defects and spin structures [28][29][30][31][32][33][34]. Consequently, it is of particular interest to explore the effects of long-rang and anisotropic DDI on such a spin-orbit coupled system, which has recently drawn considerable attentions.…”
Section: Introductionmentioning
confidence: 99%
“…Our model system consists of two 87 Rb atoms in a single optical lattice site. When an external magnetic (B) field is suddenly reversed, the initially polarized spin state will make transitions to other states, causing the transfer of spin angular momentum to orbital angular momentum or vice versa, as was first studied for a condensate with dipolar interaction by Gawryluk et al [11]. The spin transfer dynamics are shown to be controllable by an added time modulated B field.…”
mentioning
confidence: 94%
“…In the system composed of 52 Cr atoms [25][26][27][28] Feshbach resonances can enhance the effect of dipole-dipole forces. It was suggested in [29][30][31][32][33], and confirmed in [34], that dipolar effects may be observed also in the spinor F = 1 87 Rb BEC. The existence of long-range interactions is a motivating factor for studing systematically the effect of dipolar interactions on the level of squeezing in the simplest F = 1 spinor BECs.…”
Section: Introductionmentioning
confidence: 99%